Challenges and Opportunities of Implementing Education Technology in Rural and Underserved Areas of Tanzania, Assessing the Sustainability and Educational Impact of Such Initiatives - Mwinyi, Hassan (African Journal of Education and Practice, 2024)
Purpose: The aim of the study was to analyze the challenges and opportunities of implementing education technology in rural and underserved areas of Tanzania, assessing the sustainability and educational impact of such initiatives. Methodology: This study adopted a desk methodology. A desk study research design is commonly known as secondary data collection. This is basically collecting data from existing resources preferably because of its low cost advantage as compared to a field research. Our current study looked into already published studies and reports as the data was easily accessed through online journals and libraries. Findings: The implementation of education technology in rural and underserved areas of Tanzania presents both challenges and opportunities. Key challenges include limited access to reliable electricity and internet connectivity, a lack of digital literacy among teachers and students, and insufficient infrastructure and resources to support tech-based learning. Unique Contribution to Theory, Practice and Policy: Diffusion of innovation theory, unified theory of acceptance and use of technology (UTAUT) & socio-constructivist learning theory may be used to anchor future studies on the challenges and opportunities of implementing education technology in rural and underserved areas of Tanzania, assessing the sustainability and educational impact of such initiatives. Teachers should receive ongoing, hands-on training to integrate digital tools into their pedagogy, which would enhance both teaching effectiveness and student engagement. Policies should incentivize telecommunication companies to offer affordable data packages for educational purposes and extend mobile learning platforms to areas with limited connectivity.